ANALYSIS OF CODE-SWITCHING (ENGLISH-BALINESE) UTTERANCES IN THE TICKET TO PARADISE MOVIE - Fitriyah, Aidatul; Segoh, David (Jurusan Sastra Indonesia, 2024)
An American romantic comedy, Ticket to Paradise Movie, provides a unique context for investigating code-switching. It portrays a divorced couple collaborating to disrupt their daughter’s wedding in Bali. Beyond its entertaining storyline, the movie features a multilingual phenomenon, with characters utilizing the Balinese language for authenticity. This study aims to analyse the types and Reasons for Code-Switching. This study uses a qualitative approach. The primary data was collected from film transcripts and secondary data from literature reviews. The result of this study reveals the types and reasons for code-switching utterances in the Ticket to Paradise Movie. This study can contribute to broader language use comprehension in multilingual settings by exploring code-switching in this cinematic context.